Perenniporia eugeissonae sp. nov., a new species on palm discovered from Malaysia - Du, Ping; Wang, Chao-Ge; Tian, Xue-Mei (Phytotaxa, 2020)
Perenniporia eugeissonae sp. nov. is described from Malaysia, growing on palm tree. Phylogenetic inferences based on ITS and nrLSU regions revealed that it nested within the Perenniporia s.s. clade. Perenniporia eugeissonae is characterized by annual, resupinate basidiocarps, a white to cream hymenophore, small circular pores (6–8 per mm), a dimitic hyphal system with strongly dextrinoid and cyanophilous skeletal hyphae, presence of dendrohyphidia at the dissepiments, and ellipsoid, strongly dextrinoid and cyanophilous basidiospores, and growing so far exclusively on the palm Eugeissona tristis.